Wyznacz wyrażenie W = 3S - 4T. Oblicz wartość tego wyrażenia dla x = 1.
S = 2x^5 - 6x^4 - x^2 + 4x
T = 1,5x^5 - x^4 + 3x^2 + 3x - 1


Odpowiedź :

[tex]w = 3(2 {x}^{5} - 6 {x}^{4} - {x}^{2} + 4x) - 4(1.5 {x}^{5} - {x}^{4} + 3 {x}^{2} + 3x - 1) = 6 {x}^{5} - 18 {x}^{4} - 3 {x}^{2} + 12x - (6 {x}^{5} - 4 {x}^{4} + 12 {x}^{2} + 12x - 4) = 6 {x}^{5} - 18 {x}^{4} - 3 {x}^{2} + 12x - 6 {x}^{5} + 4 {x}^{4} - 12 {x}^{2} - 12x + 4 = - 14 {x}^{4} - 15 {x}^{2} + 4[/tex]

[tex]x = 1[/tex]

zatem

[tex] - 14 \times {1}^{4} - 15 \times {1}^{2} + 4 = - 14 - 15 + 4 = - 29 + 4 = - 25[/tex]

mam nadzieję, że pomogłam